Evidence for a Common Founder and Clinical Characteristics of Japanese Families with the MAPT R406W Mutation - Takeshi Ikeuchi; Toru Imamura; Yasuhiro Kawase; Yoshimi Kitade; Miyuki Tsuchiya; Takayoshi Tokutake; Kensaku Kasuga; Ryuji Yajima; Tamao Tsukie; Akinori Miyashita; Morihiro Sugishita; Ryozo Kuwano; et al. (Dementia and Geriatric Cognitive Disorders Extra, 2011)
Background/Aim: Mutations in MAPT cause frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17). Patients with the MAPT R406W mutation were reported to show phenotypic heterogeneity in different ethnic backgrounds. We here report the clinical and genetic characteristics of Japanese families with the R406W mutation. Methods: We examined the clinical and neuroimaging features of 6 patients from three families with the R406W mutation. We determined the genotypes of intragenic MAPT single-nucleotide polymorphisms (SNPs) and the flanking microsatellite markers to search for a common founder. Results: The initial symptom was memory loss with the average age at onset being 54 years. Anterograde amnesia with episodic memory impairment was the predominant phenotype. Behavioral and personality changes or parkinsonism is not a prominent feature. A brain MRI study revealed marked atrophy of the medial temporal lobe. Genetic analysis of SNPs and microsatellite markers revealed that the affected members of the three families share common genotypes. Conclusion: The findings of the affected members in this study, which corroborate previously reported findings of European families, suggest that the R406W mutation may represent a phenotype of predominant anterograde amnesia in FTLD-17. Our genetic data suggest that a founder effect may account for some families with the R406W mutation.